Studying genetic resources of spring bread wheat in the environments of Northern Kazakhstan - A. T. Babkenov; S. A. Babkenova; E. K. Kairzhanov (Труды по прикладной ботанике, генетике и селекции)
Background. Spring bread wheat is the main export crop in Kazakhstan. Unfortunately, wheat varieties cultivated for large-scale production do not fully meet the requirements of agricultural producers. The world diversity of wheat genetic resources should be widely used in breeding programs in order to develop new wheat cultivars with stable yields and with resistance to adverse environmental factors.Materials and methods. One hundred collection accessions of spring bread wheat were studied in 2015–2017 at the A.I. Barayev Science and Production Center of Grain Farming, Ltd. Seeds were sown at an optimum time (May 20–25), using an SSFC-7 seeder. Harvesting was conducted with a Wintersteiger combine. The study of the collection material was carried out in accordance with the guidelines developed by the N.I. Vavilov Institute of Plant Genetic Resources (VIR). The protein content was measured in line with State Standard 10846-91. The method of sodium dodecyl sulfate (SDS) sedimentation, modified by V. M. Bebyakin and M. V. Buntina, was used to measure the level of sedimentation.Results and conclusion. During the three-year study of spring bread wheat accessions in Northern Kazakhstan, only the cultivars ‘Shortandinskaya 2012’ and ‘Astana 2’ exceeded the reference ‘Astana’ in yield. The accessions ‘BW 252’, ‘Neepawa’ (Canada), ‘MANITUOU LR 13’ (CIMMYT, Mexico) and ‘Novosibirskaya 29’ (Russia) ripened 1–2 days earlier than the reference, while their average yield for 3 years was almost on the same level with the reference. The cultivars ‘Astana’ (the reference, Kazakhstan), ‘WA007824 WA7824’ (USA), ‘Novosibirskaya 29’, ‘Novosibirskaya 15’ (Russia), ‘OPATA85 LR10’ and ‘LR27+LR31,LR34’ (CIMMYT, Mexico) were distinguished for grain quality due to their high protein content and the level of sedimentation.